Psychological factors predict an unfavorable pain trajectory after hysterectomy: a prospective cohort study on chronic postsurgical pain - Pinto, Patrícia Jesus Ribeiro (2018)
Chronic postsurgical pain (CPSP) is a well-recognized potential complication with negative personal, social, and health care consequences. However, limited data exist on CPSP and on the course of pain over time after hysterectomy. Using data from a prospective cohort study on a consecutive sample assessed at 4 time points, presurgery (T1), 48 hours (T2), 4 months (T3), and 5 years postsurgery (T4), we sought to examine women's PSP trajectories using assessments of pain at T3 and T4. In addition, this study aimed to investigate presurgical and postsurgical risk factors associated with an unfavourable pain trajectory (PT). Based on pain data collected at T3 and T4, 3 distinct trajectories of PSP emerged: no CPSP (PT1; n = 88), prolonged PSP (PT2; n = 53), and CPSP (PT3; n = 29). Moreover, reported CPSP prevalence at 5 years was 17.1%. Multinomial logistic regression models controlling for age, presurgical pain, and type of hysterectomy tested for baseline and acute postsurgical predictive variables. Membership in PT2 and PT3 was predicted by presurgical anxiety (odds ratio [OR] = 1.131, P = 0.015; OR = 1.175, P = 0.009, respectively), emotional representation of the surgical disease (OR = 1.155, P = 0.034; OR = 1.213, P = 0.020, respectively), and pain catastrophizing (OR = 1.079, P = 0.043; OR = 1.143, P = 0.001, respectively). Furthermore, acute PSP intensity and frequency determined membership of women in PT3 (OR = 1.211, P = 0.033; OR = 3.000, P = 0.029, respectively), and postsurgical anxiety (OR = 1.182, P = 0.026) also played a key predictive role. This study identified factors that can be easily screened before and after surgery and are amenable to change through carefully designed timely and tailored interventions for women at risk of an unfavorable PSP trajectory posthysterectomy.